Peri-acetabular bone mineral density in total hip replacement. Issue 8 (August 2013) - Gauthier, L.; Dinh, L.; Beaulé, P. E.
Abstract : Objectives: To quantify and compare peri-acetabular bone mineral density (BMD) between a monoblock acetabular component using a metal-on-metal (MoM) bearing and a modular titanium shell with a polyethylene (PE) insert. The secondary outcome was to measure patient-reported clinical function. Methods: A total of 50 patients (25 per group) were randomised to MoM or metal-on-polyethlene (MoP). There were 27 women (11 MoM) and 23 men (14 MoM) with a mean age of 61.6 years (47.7 to 73.2). Measurements of peri-prosthetic acetabular and contralateral hip (covariate) BMD were performed at baseline and at one and two years' follow-up. The Western Ontario and McMaster Universities osteoarthritis index (WOMAC), University of California, Los Angeles (UCLA) activity score, Harris hip score, and RAND-36 were also completed at these intervals. Results: At two years, only zone 1 showed a loss in BMD (-2.5%) in MoM group compared with a gain in the MoP group (+2.2%). Zone 2 showed loss in both groups (-2.2% for MoM; -3.9% for MoP) and zones 3 and 4 a gain in both groups (+0.1% for MoM; +3.3% for MoP). No other between-group differences were detected. When adjusting for BMD of the contralateral hip, no differences in BMD were observed. The only significant differences in functional scores at two years were higher UCLA activity (7.3 (sd 1.2) vs 6.1 (sd 1.5); p = 0.01) and RAND-36 physical function (82.1 (sd 13.0) vs 64.5 (sd 26.4); p = 0.02) for MoM bearings versus MoP. One revision was performed in the MoM group, for aseptic acetabular loosening at 11 months. Conclusions: When controlling for systemic BMD, there were no significant differences between MoM and MoP groups in peri-acetabular BMD. However, increasing reports of adverse tissue reactions with large head MoM THR have restricted the use of the monoblock acetabular component to resurfacing only.